Local Level Perception of Corruption: An Anthropological Inquiry - Kattel, Sewanta (Dhaulagiri Journal of Sociology and Anthropology, 2010)
The underlying problem of corruption in Nepal at the micro level stems from the 'capture' of the sustainable number of the policies and implementing rules and regulations of the different laws by vested interests. The long standing collusion between political parties and government officials has resulted in a destructed economy that favors private economic interests over the broader public goods. The situation is compounded by the patterns of non transparent and illegitimate practice that sustain the culture of corruption. Sources of income for individual and employees are unregulated and often arbitrarily determined through the patronage system that is link to the culture of silence underpinning such patronage. The role of civil society is to controlling corruption by working at the grass roots political and bureaucratic, and legal judicial level. Key words: Civil society; problem; power; judicial; corruption DOI: 10.3126/dsaj.v3i0.2785 Dhaulagiri Journal of Sociology and Anthropology Vol.3 2009 163-174